Atasi Kecemasan dengan Teknik Distraksi, Relaksasi Nafas dalam dan Hipnotis 5 Jari - Jober, Naomi Frolinda; Sinaga, Eva (Jurnal Medika: Medika, 2025)
This community service focuses on health education aimed at teaching anxiety management techniques through distraction techniques, deep breathing relaxation, and five-finger hypnosis for patients with mental disorders at RSJD Abepura. This program is conducted as part of a collaboration between Cenderawasih University, the Nursing Science Program, and RSJD Abepura to fulfill the Tri Dharma of Higher Education through community service and to improve the quality of mental health services in Abepura. The educational methods include lectures, simulations, and interactive discussions with participants, including patients and their families. Results show an improvement in participants' understanding of relaxation and anxiety management techniques, evidenced by enthusiastic responses during simulations and discussions. A total of 80% of participants were able to understand and answer questions about anxiety management techniques after the session, although additional guidance is still needed for independent application of five-finger hypnosis.Further activities with more intensive guidance are required, particularly in the independent application of the five-finger hypnosis technique, to enhance the skills and confidence of patients and their families in managing anxiety independently. Additionally, increasing the duration and frequency of training sessions would be beneficial in deepening the understanding of relaxation techniques, which may contribute to reducing the anxiety rate among patients at RSJD Abepura